2021
DOI: 10.1177/03000605211060144
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-1β rs1143634 (+3954C>T) polymorphism in cancer risk: an updated meta-analysis and trial sequential analysis

Abstract: Objective Oxidative stress caused by the pro-inflammatory cytokine interleukin (IL)-1β has been widely investigated for cancer risk. In this study, we focused on the role of IL-1β rs1143634 polymorphism to reveal its impact on cancer development. Methods Related studies with fixed inclusion criteria were selected from electronic databases to May 2021. This meta-analysis was performed with odds ratios and 95% confidence intervals. Heterogeneity, publication bias and sensitivity analyses were also conducted. Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…These associations highlight their potential roles in maintaining liver health and immune system support. The associations found in our study are consistent with the results of other similar studies, where gene function and SNP associations suggest a multifactorial approach through different mechanisms or platforms and have been discussed in common pathophysiological pathways [ 11 , 13 , 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…These associations highlight their potential roles in maintaining liver health and immune system support. The associations found in our study are consistent with the results of other similar studies, where gene function and SNP associations suggest a multifactorial approach through different mechanisms or platforms and have been discussed in common pathophysiological pathways [ 11 , 13 , 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…This is a synonymous variant (p.Phe105=) reported in ClinVar [23] as associated with antisynthetase syndrome and endometriosis. Jafrin, Aziz, & Islam (2021) performed a meta-analysis which revealed that the presence of this polymorphism increases the risk of cancer development, more precisely gastric and breast cancers and multiple myeloma, especially in Asian populations [24]. Several studies connect rs1143634 with chronic periodontitis, including a meta-analysis by da Silva et al (2017), in which it was signi cantly associated with chronic periodontitis disease in Caucasian, Asian and mixed populations [25].…”
Section: Discussionmentioning
confidence: 99%
“…This is a synonymous variant (p.Phe105=) reported in ClinVar ( Landrum et al, 2018 ) as associated with antisynthetase syndrome and endometriosis. Jafrin, Aziz and Islam (2021) performed a meta-analysis which revealed that the presence of this polymorphism increases the risk of cancer development, more precisely gastric and breast cancers and multiple myeloma, especially in Asian populations ( Jafrin et al, 2021 ). Several studies connect rs1143634 with chronic periodontitis, including a meta-analysis by da Silva et al (2017) , in which it was significantly associated with chronic periodontitis disease in Caucasian, Asian and mixed populations ( da Silva et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%